Preferensi Mahasiswa Universitas Muhammadiyah Surakarta Tentang Valentine's Day Ditinjau Dari Sudut Pandang Ekonomi, Sosial, Dan Religi - Rusiyawati, Iga; , Siti Fatimah SE, M.Si (2016)
Respondents in this study are students of University of Muhammadiyah Surakarta numbering 25391, 300 samples were taken with a combination of Convenience sampling method and proportional sampling based on quotas. Descriptive analysis showed that of the 300 respondents, 26 respondents (8.7%) who celebrate Valentine's Day, and 275 respondents (91.3%) did not celebrate Valentine's day. Judging from the background of the economic income of parents of students, from 26 students who celebrate Valentine's Day with the highest percentage of revenue <3 million as many as 12 people (46.2%), and the lowest-income> 5 million as many as 6 people (23,1) , Judging from the social point of view of students, most activities of the students who make the celebration of Valentine's Day is shopping (27%) and traveling (53.8%). Viewed from the standpoint of religious students who celebrate Valentine's, there are 2 (7.7%) students who were loyal to religious orders and less obedient as many as 23 people (88.5%). This research is expected to provide information to the University of Muhammadiyah Surakarta especially Islamic studies institute, in order to take out a policy in the educational system of Al-Islam to meghimbau students not to follow the tradition of Valentine's Day. If you need any fatwa that prohibits it because valentine is part of the symbols of Christian religion.